Risk Factors for Anthracycline-Induced Cardiotoxicity - Qiu, Shuo; Zhou, Tian; Qiu, Bo; Zhang, Yuxin; Zhou, Yonggang; Yu, Huihui; Zhang, Jingyi; Liu, Li; Yuan, Lijun; Yang, Guodong; Duan, Yunyou; Xing, Changyang (Frontiers in Cardiovascular Medicine, 2021)
Background: Several cardiovascular risk factors have been suggested to be associated with anthracycline-induced cardiotoxicity, but their quantitative effects have not reached a consensus. Methods: We searched PubMed, EMBASE, and Cochrane Library databases for manuscripts published from inception to February 2021, which reported the results of cardiotoxicity due to anthracycline chemotherapy without trastuzumab. Cardiotoxicity defined by any reduction of left ventricular eject fraction (LVEF) to below 50% or a >10% reduction from baseline was defined as the primary endpoint. Odd ratios (OR) with 95% confidence intervals (CI) were calculated using a random-effects model meta-analysis. Results: A total of 7,488 patients receiving anthracycline chemotherapy without trastuzumab were included, who had at least one risk factor at baseline. Hypertension (OR: 1.99; 95% CI: 1.43–2.76), diabetes mellitus (OR: 1.74; 95% CI: 1.11–2.74), and obesity (OR: 1.72; 95% CI: 1.13–2.61) were associated with increased risk of cardiotoxicity. In addition, the relative reduction of global longitudinal strain (GLS) from baseline after anthracycline treatment could significantly improve the detection ability of cardiotoxicity (28.5%, 95% CI: 22.1–35.8% vs. 16.4%, 95% CI: 13.4–19.9%) compared with LVEF. The early detection rate of anthracycline-induced cardiotoxicity (3 months after chemotherapy) by GLS was 30.2% (95% CI: 24.9–36.1%), which is similar with the overall result of GLS. Conclusions: Hypertension, diabetes mellitus, and obesity are associated with increased risk of anthracycline-induced cardiotoxicity, which indicates that corresponding protective strategies should be used during and after anthracycline treatment. The findings of higher detection rate and better early detection ability for cardiotoxicity than LVEF added new proofs for the advantages of GLS in detection of AIC.